A new global kinematic-optical-thermal process model for laser-assisted tape winding with an application to helical-wound pressure vessel. (August 2020) - Hosseini, S.M. Amin; Schäkel, Martin; Baran, Ismet; Janssen, Henning; van Drongelen, Martin; Akkerman, Remko
Abstract: A new global kinematic-optical-thermal (KOT) model is proposed to provide a proper understanding and description of the temperature evolution during laser-assisted tape winding and placement (LATW/LATP) on any arbitrary shaped tooling geometry. Triangular facets are utilized in the kinematic model to define a generic tooling together with a user-defined fiber path and time-dependent process settings such as the tape feeding rate. The time-dependent heat flux distribution on the surfaces is calculated by the optical model and subsequently coupled to the thermal model. The numerical implementation of the developed KOT model is first verified for process simulations of the LATP on a flat tooling by comparing the temperature predictions with the available literature data. To validate the KOT model, a total of four pressure vessels are manufactured with in-line temperature measurements. The process temperature predictions are found to agree well with the measured temperature during the helical winding. The influence of the changing tooling curvature and process speed on the process temperature is found to be significant as shown by the experimental and numerical findings. Graphical abstract: Unlabelled Image Highlights: A new laser-assited tape winding process tool considering arbitrary tooling, fiber path and process settings was developed. The temperature measurements during the helical winding of a doubly-curved dome was used to validated the model. The changing substrate curvature had a significant influence on the processing temperature. The processing temperature history was mapped on the product profile visualizing the location of critical points.